A Chinese String matching Algorithm Based on Edit Distance for Electric Power Customer Service. Issue 5 (March 2020) - Liu, Xusheng; Mu, Songhe; Li, Zhiming; Yang, Zixing; Han, Wei; Wang, Zhiwei
Abstract: With the rapid development of information technology, electric power customer service needs to extract accurate information from the data centre to provide customers urgently. String matching is the most straightforward solution. There are some problems in the editing distance definition of traditional string matching algorithm when dealing with Chinese text. In this paper, the pronunciation characteristic of Chinese characters is integrated in the definition of edit distance and a string matching algorithm based on edit distance for electric power customer service data centre is proposed. Finally, through simulation analysis, we demonstrate that this algorithm has good reliability when dealing with Chinese string matching problem. Thus, it is suitable for electric power customer service to obtain the target string.